2016
DOI: 10.1002/cphc.201501072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal Oxides on Platinum Activity towards Methanol Oxidation in H2SO4 solution

Abstract: Pt-CeO2 /C, Pt-TiO2 /C, and Pt-ZrO2 /C electrocatalysts were prepared by using a modified microwave-assisted polyol process. Physical characterization was performed by using XRD, TEM, and EDX analyses. The incorporation of different metal oxides increased the dispersion degree of Pt nanoparticles and reduced their diameter to 2.50 and 2.33 nm when TiO2 and ZrO2 were introduced to Pt/C, respectively. The electrocatalytic activity of various electrocatalysts was examined towards methanol oxidation in H2 SO4 solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 75 publications
(133 reference statements)
0
10
0
Order By: Relevance
“…Recently, the activity of Pt electrocatalysts was improved by adding metal oxides, sulfides, carbides, and nitrides as promoters . Among them, metal‐oxide promoters are more efficient because they provide hydroxy sources for removal of carbonaceous species, such as adsorbed CO (CO ads ), at lower potentials . Also, metal oxides stabilize Pt crystallites and avoid their random growth and accumulation during device operation for longer times.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the activity of Pt electrocatalysts was improved by adding metal oxides, sulfides, carbides, and nitrides as promoters . Among them, metal‐oxide promoters are more efficient because they provide hydroxy sources for removal of carbonaceous species, such as adsorbed CO (CO ads ), at lower potentials . Also, metal oxides stabilize Pt crystallites and avoid their random growth and accumulation during device operation for longer times.…”
Section: Introductionmentioning
confidence: 99%
“…Also, metal oxides stabilize Pt crystallites and avoid their random growth and accumulation during device operation for longer times. So far, Ru, Ce, Ti, V, Nb, Mo, W, Zr, Sn, Mn, Fe, Ni, and Co oxides have been studied as promoters to Pt‐based catalysts for the electrooxidation of alcohols . Among these oxides, vanadium(V) oxide (V 2 O 5 ) is a promising material for the electrocatalytic oxidation of alcohols .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These merits indicate that the modified electrodes show remarkable electro‐catalytic activity for electro‐oxidation of methanol. Notably, the bare CPE showed negligible catalytic activity . Comparing CVs of the modified electrodes (Figure c) showed that the intensity of the oxidation peak currents located at 0.20 V for BSNCF/CPE electrode is 4.24 mA/cm 2 higher than that of BSCF/CPE (3.45 mA/cm 2 ) located at 0.25 V, suggesting that the electro‐catalytic activity for methanol oxidation of the former is higher than that of the latter.…”
Section: Resultsmentioning
confidence: 99%